Exploring Learning Agility in Education: The Effect of Teachers' Learning Agility on Their Readiness for Change and Performance - Yazıcı, Şebnem; Özgenel, Mustafa; Özgenel, Mustafa (Abant İzzet Baysal Üniversitesi, 2024)
Learning agility is the ability to learn from experiences and to apply these learnings rapidly and successfully in the event of new problems. This research aims to reveal whether the learning agility of teachers in Turkey had an impact on their readiness for change and performance. The explanatory sequential research design was adopted to further clarify the relationship between the variables. The quantitative phase of the study was conducted on a sample group consisting of 1640 teachers working in public schools in Istanbul. Subsequently, data were obtained through semi-structured interviews from 21 teachers working in public schools, and the data were analyzed by content analysis. According to the quantitative research findings, teachers' learning agility positively affects readiness for change and performance. The qualitative findings of the study revealed that teachers developed their learning agility through training, research and experience. It has been determined that teachers with high learning agility are open-minded and ready for change. Teachers achieve speed and flexibility in classroom practices by finding solutions to the problems brought about by change. In addition, unlike the quantitative findings, the qualitative findings revealed that teachers were not sufficiently prepared for change and even showed resistance to change. The findings provide clues about teachers' professional development and educational reform and change initiatives.

Öğrenme çevikliği, deneyimlerinden öğrenebilme ve bu öğrenmeleri yeni problemler karşısında hızlı ve başarılı bir şekilde uygulama becerisidir. Bu araştırma, Türkiye’deki öğretmenlerin öğrenme çevikliğinin, değişime hazır olma durumlarına ve performanslarına etkisi olup olmadığını ortaya çıkarmayı amaçlamıştır. Değişkenler arasındaki ilişkiyi daha fazla açıklığa kavuşturmak için araştırma deseni olarak açıklayıcı sıralı desen benimsenmiştir Araştırmanın nicel aşaması İstanbul’da kamu okullarında görev yapan 1.640 öğretmenden oluşan örneklem grubu üzerinde gerçekleştirilmiştir. Daha sonra kamu okullarında görev yapan 21 öğretmenden yarı yapılandırılmış görüşmeler yoluyla elde edilen veriler içerik analizi yapılarak çözümlenmiştir. Nicel araştırma bulgularına göre öğretmenlerin öğrenme çevikliği, değişime hazır olma durumunu ve performansı olumlu yönde etkilemektedir. Araştırmanın nitel bulguları öğretmenlerin eğitim, araştırma ve deneyim yoluyla öğrenme çevikliklerini geliştirdiklerini ortaya koymuştur. Yüksek öğrenme çevikliğine sahip öğretmenlerin değişime karşı açık fikirli ve hazır oldukları tespit edilmiştir. Öğretmenler, değişimin getirdiği problemler karşısında çözüm yolları üreterek sınıf içi uygulamalarda hız ve esnekliğe ulaşmaktadır. Ayrıca nitel bulgular, nicel bulgulardan farklı olarak öğretmenlerin değişime karşı yeterince hazır olmadıkları, hatta değişime direnç gösterdikleri tespit edilmiştir. Bulgular, öğretmenlerin mesleki gelişimi, eğitim reform ve değişim girişimleri hakkında ipuçları sunmaktadır.
Eğitimde Öğrenme Çevikliğini Keşfetmek: Öğretmenlerin Öğrenme Çevikliğinin Değişime Hazır Olma Durumlarına ve Performanslarına Etkisi
Keywords: Learning agility; Readiness for change; Teacher performance; Öğrenme çevikliği; Değişime hazır olma; Öğretmen performansı